2007
DOI: 10.1021/jm061425k
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of Inhibitors for Severe Acute Respiratory Syndrome 3C-Like Protease Based on Phthalhydrazide Ketones or Heteroaromatic Esters

Abstract: The 3C-like protease (3CLpro), which controls the severe acute respiratory syndrome (SARS) coronavirus replication, has been identified as a potential target for drug design in the treatment of SARS. A series of tetrapeptide phthalhydrazide ketones, pyridinyl esters, and their analogs have been designed, synthesized, and evaluated as potential SARS 3CLpro inhibitors. Some pyridinyl esters are identified as very potent inhibitors, with IC50 values in the nanomolar range (50-65 nM). Electrospray mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 34 publications
3
67
0
1
Order By: Relevance
“…A shift of approximately 217 Da was observed after treatment of SARS-CoV 3CLpro with the inhibitor confirming covalent modification. Covalent modification by similar reactive esters has also been reported 13a,20.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…A shift of approximately 217 Da was observed after treatment of SARS-CoV 3CLpro with the inhibitor confirming covalent modification. Covalent modification by similar reactive esters has also been reported 13a,20.…”
mentioning
confidence: 57%
“…It seems the indole-5-carboxylate moiety plays an important role in binding with the enzyme active site. Another class of hetereoaromatic ester inhibitors was also identified and studied 12, 13. The 5-chloropyridine moiety in 4 proved to be the key unit for the activity against 3CLpro.…”
mentioning
confidence: 99%
“…Virtual screening (Plewczynski et al, 2007;Mukherjee et al, 2008;Nguyen et al, 2011) or a high-throughput screening of small molecule libraries have identified inhibitorsincluding an anti-HIV agent and serotonin antagonist, cinanserin (Blanchard et al, 2004;Kao et al, 2004;Wu et al, 2004a;Chen et al, 2005). Other 3CL protease inhibitors identified so far belongto categories such as plant derived phenolic or flavonoid compounds (Lin et al, 2005;Nguyen et al, 2012), active site, nonactive site or competitive inhibitors (Kaeppler et al, 2005;Lee et al, 2005;Du et al, 2007;Ryu et al, 2010), ketones or ester based inhibitors (Goetz et al, 2007;Zhang et al, 2007;Ghosh et al, 2008;Shao et al, 2008;Verschueren et al, 2008;Zhang et al, 2008), modified peptidomimetic inhibitors (Ghosh et al, 2007), metal conjugated inhibitors (Lee et al, 2007;…”
Section: Viral Protease Inhibitorsmentioning
confidence: 99%
“…1,4,8,11- temperature for ca. 18 h. The solvent was evaporated to give a yellow solid which was used without further purification [29]. To a solution of XX (Scheme 2) [30] (80 mg, 0.14 mmol) in DMF (5 mL) was added 1H-pyrrole-2-carbonyl chloride (18.3 mg, 0.14 mmol) and the mixture stirred at room temperature until no starting materials could be detected by LC-MS and a molecular ion consistent with the desired monosubstituted product was observed (ca.…”
Section: Reagentsmentioning
confidence: 99%